Investigation of Aquifer Zone in Tambakromo Village, Ponjong Subdistrict, Gunung Kidul Regency, Yogyakarta, Indonesia - Al Hussein Flowers Rizqi; Oky Sugarbo (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
The presence of surface water is always being a primary issue in Gunung Kidul regency. An aquifer investigation would support groundwater exploration. The research area is located in Tambakromo village, Ponjong subdistrict, Gunung Kidul Regency, Daerah Istimewa Yogyakarta Province. The aim of this research is about geological and subsurface conditions based on geological data and geoelectrical resistivity methods. By resistivity value interpretation, the position, depth, and thickness of aquifer could be determined. The purpose of this research is to identification of geological conditions that supported being aquifer rock. The method in this research is used geological mapping combined with petrographic analysis. The geophysics method is used to identification of aquifer in research area. Three locations were selected to acquisition geoelectrical resistivity survey. In Grogol village, there is no aquifer based on resistivity values of more than 10000 ohmmeters (andesitic breccia). An akuifuge is interpreted there in andesitic breccia instead of the presence of aquifer. The tuffaceous is interpreted as lapillistone that contained the glass with resistivity value of 43.63 and 340.11 ohmmeters. The Garon and Sumberejo village have aquifer at depth of 50 to 80 meters with a thickness of 13 to 70 meters. The type of aquifer in both area is included an unconfined aquifer, specifically located in between the limestone rock layer and andesitic breccia. By regional stratigraphic correlation, tuffaceous lapillistone is interpreted as derived from Semilir Formation. In addition, the presence of aquifer in research area could recommend for local people and government to reduce the drought disaster.